The Influence of the English Language on the Polish Youth Speak - Jagun, Anita (Respectus Philologicus, 2023)
The aim of the following article is to discuss the impact of the English language on Polish youth speak. First, the paper demonstrates databases that can be useful while analyzing the language of contemporary Polish teenagers. Next, it presents the English-origin lexical units that were classified to the final stage of the Polish Youth Word of the Year 2022 plebiscite. Finally, it highlights the similarities and differences between the use of a specific term in Polish and English. The results of the study show that the English-speaking culture has an enormous impact on how Polish teenagers communicate and perceive reality. Twelve of twenty lexical units selected in the plebiscite can be linked to the English language. Some of them loosely refer to English expressions or sounds. Many words are directly transferred from slang. They often originate from the world of computer games or social media. In today’s day and age, common access to the Internet makes them well-known in various parts of the world.
Keywords: youth speak; anglicisms; youth sociolect; Youth Language and Culture Observatory